Pharmacoeconomic evaluation of mirabegron: results of the healthcare budget impact analysis - A. S. Kolbin; I. A. Vilium; M. A. Proskurin; Yu. E. Balykina (Izdatelstvo OKI, 2018)
Overactive bladder (OAB) is a chronic disease that correlates with the age of the patient, and occurs in almost one in seven women and men. Pharmacotherapy is one of the main methods for correction of this nosology. Taking into account the absence of additional therapeutic option on the Vital and Essential Drugs List for patients with contraindications for the prescription of solifenacin and BTX-A, patients with intolerance to these drugs conduct, an analysis of the economic consequences of the use of mirabegron under the State Guarantees for Providing Free Medical Care for the OAB treatment. Approved recommendations on carrying out the budget impact analysis were used. Results of the study show, that the expansion of the mirabegron use in the treatment of patients with OAB in the target population leads to the reduction in the cost of medical therapy for this group of patients: with an increase in the share of mirabegron up to 5 %, costs will decrease by 7.8 %; with an increase in the mirabegron share up to 10 % costs will decrease by 12.5 %; when using in 15 % of the target population - by 22.3 %. Trend analysis of changes in the average weighted costs shows the following: an increase in the use of mirabegron leads to a significant reduction in total costs, the total benefit can reach 6 250 002 576 rubles per 3 years of the drug presence in the VED List, which allows attributing the OAB treatment with mirabegron to economically feasible and resource-saving medical technologies.